(untitled) (Journal of the College of Basic Education, 2020)
The current research boils down to a study of the aesthetic concepts of Plato and its contributions to European art, where Plato confirms that the conditions raised by different arts in man gradually penetrate himself into a steady nature, that is, the psychological development of one is determined by the passions that he passes through and in which the arts play a big role The research aimed to identify Plato’s aesthetic concepts and their educational contributions to European art. To reach the results, the research was divided into four chapters: the first of which represented the methodological framework for the research, during which he dealt with: the research problem which resulted in an ambiguous question: What are the aesthetic concepts of Plato and what are their educational implications in European art, so that the aim of the research is to get to know the concepts Plato’s aesthetic and her educational contributions to European art. The researcher also listed the importance of this research with two points, the most important of which was the research offer to the researchers in the field of aesthetics and art philosophy at the artistic and educational level. The research also included the limits of the spatial, temporal and objective research as well as defining the terms (concept, aesthetic, and education). As for the second chapter, it included the theoretical framework for research, and it consisted of two subjects, the first of which concerned me with studying Plato’s aesthetic concepts, while the second chapter was devoted to studying patterns of education. As for the third chapter, it represents the research procedures. The research and sample community included the two technical works chosen by the researcher and the sample analysis to extract the aesthetic and educational mechanisms and works in them. While the fourth semester included the results and it was the most important of them: Education for Plato has a special place. Plato has succeeded in achieving a balance in emphasizing the educational aspect of art, as he celebrated the development of aesthetic taste as a basic factor in citizen education and its formation of a decent human being. These aesthetic and educational concepts were reflected in the samples (1) and (2). Plato emphasized the important role that education plays in building a utopia, so it emphasizes the need for legislators to be interested in raising young adults, and he believed that it is possible to transfer these systems and educational values ​​through art. Also this chapter contained the conclusions reached by the researcher, namely: Through his philosophical propositions, Plato succeeded in achieving a balance in emphasizing the educational aspect in art. He also celebrated the development of aesthetic taste as a basic factor in the education of the citizen and his decent formation in man. These aesthetic and educational concepts were reflected in art. Education is a human necessity, as education achieves the integrated growth of an individual’s personality from his ability to learn to his death.